Antidiabetic Activity of Catharsntus Pusillus: A Review - Asija, Rajesh; Swami, Amandeep; Saini, Manoj Kumar (Journal of Biomedical and Pharmaceutical Research, 2023)
For centuries, diabetes and its variants have been a familiar illness to medical professionals. Being a lifestyle disease, diabetes necessitates extensive research into the physiological effects of insulin as well as its various clinical manifestations, including tissue complications. It is important to emphasize the importance of appropriate treatment in terms of diet and anti-diabetic medications. Herbal diabetes treatments are not new, in actuality. As early as 1550 B.C., plants and plant extracts were used to treat the illness; up to 400 plants were "prescribed" before the creation of potent diabetes drugs earlier this century. An attempt has been made in this paper to provide an overview of some Indian plants that have been studied for their antidiabetic properties, along with information on their phytoconstituents and mechanism of action. This endocrine system metabolic disorder affects approximately 10% of the global population, and the number of affected individuals rises daily. The profiles that are displayed contain details about the plant parts and test model that were utilized, the scientific and family names, the level of hypoglycemic activity, and the active chemical agents. These plants’ effects have the potential to correct metabolic abnormalities and postpone the onset of diabetic complications. This study encourages more investigation into the possible applications of therapeutic plants with antidiabetic properties. Keywords: Antidiabetic, Hypoglycemic, Phytoconstituents, Clinical, Endocrine